Relationships between central corneal thickness and optic disc topography in eyes with glaucoma, suspicion of glaucoma, or ocular hypertension - Pinakin Gunvant (Dove Medical Press, 2008)
Pinakin Gunvant1, Lucia Porsia2, Russell J Watkins3, Henrietta Bayliss-Brown2, David C Broadway21Department of Research, Southern College of Optometry, Memphis, TN, USA; 2Department of Ophthalmology, Norfolk and Norwich University Hospital NHS Trust, Norwich, UK; 3Department of Pathology, Algernon Firth Buildings, Leeds General Infirmary, Leeds, UKPurpose: To identify relationships between central corneal thickness (CCT) and optic disc topography, as determined by scanning laser ophthalmoscopy (SLO), for patients seen in a specialist glaucoma service.Methods: 272 eyes of 144 patients with primary open angle glaucoma (POAG; n = 71), normal tension glaucoma (NTG; n = 50), ocular hypertension (OH; n = 48) and those considered to be suspicious for glaucoma (GS; n = 103) underwent ultrasonic pachymetry and optic disc topography by SLO. Correlations between CCT and SLO parameter values were identified. A Bonferroni correction for multiple comparisons was performed and a p value of 0.0042 was considered significant.Results: Mean CCT values were 533 μm (POAG), 530 μm (NTG), 550 μm (GS), and 565 μm (OH). As a group the GS and OH eyes had signifi cantly thicker CCT values than eyes with POAG. In addition, the NTG eyes had signifi cantly thinner CCT values than GS and OH eyes. Overall multiple SLO parameters correlated with CCT even after accounting for co-variance with age, refraction and inclusion of both eyes. Sub-group analysis indicated that ‘optic disc rim area’ positively correlated with CCT (r = 0.378) and ‘cup to disc area ratio’ negatively correlated with CCT (r = −0.370) in the POAG group. In the GS group the parameter ‘area below reference’ (a measure of cup volume) and ‘mean cup depth’ had negative correlations with CCT (r = −0.297 and −0.323) indicating that eyes with thinner than average corneal thickness measurements had larger and deeper cups.Conclusion: Thinner corneas appear to be associated with larger and deeper optic disc cups in the eyes of patients seen in a specialist glaucoma service.Keywords: central corneal thickness, optic disc topography, optic disc compliance, glaucoma